2007
DOI: 10.1007/s11060-007-9396-1
|View full text |Cite
|
Sign up to set email alerts
|

The lack of expression of the peripheral benzodiazepine receptor characterises microglial response in anaplastic astrocytomas

Abstract: The peripheral benzodiazepine receptor (PBR) is a 18 kDa molecule mainly involved in cholesterol transport through the mitochondrial membrane. In microglia, PBR is expressed from the earliest stages of activation and appears to exert a pro-inflammatory function. This molecule is commonly up-regulated in inflammatory, degenerative, infective and ischaemic lesions of the central nervous system but it has never been reported in glioma-infiltrating microglia. We examined two anaplastic astrocytomas showing minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…This tumor was a transforming astrocytoma in which anaplastic features were limited to a small component of the lesion, and the overall TSPO expression was as low as LGAs. Our results on tissue are consistent with previous studies that used immunohistochemistry to investigate TSPO in human astrocytomas (31,32) and documented variability in TSPO expression and some degree of overlap between WHO grade II and III lesions.…”
Section: Discussionsupporting
confidence: 92%
“…This tumor was a transforming astrocytoma in which anaplastic features were limited to a small component of the lesion, and the overall TSPO expression was as low as LGAs. Our results on tissue are consistent with previous studies that used immunohistochemistry to investigate TSPO in human astrocytomas (31,32) and documented variability in TSPO expression and some degree of overlap between WHO grade II and III lesions.…”
Section: Discussionsupporting
confidence: 92%
“…Our experiments demonstrated that GAMs contribute minimally to TSPO expression in gliomas [25]. TSPO down-regulation in GAMs is particularly interesting and seems unique to gliomas confirming the results published by Takaya et al [14]. GAMs are known to increase substantially with tumour grade in astrocytomas and their morphology to be consistent with an activate state but they switch to a M2 phenotype with impairment of their cytotoxicity, antigen presentation and phagocytosis.…”
Section: Tspo Expression In Glioma-associated Microglia and Macrophagessupporting
confidence: 90%
“…Both authors suggested a correlation between TSPO expression and outcome. Previously, Takaya et al [14] combined PET-imaging and neuropathology and observed low TSPO expression in two cases of anaplastic astrocytoma (AA) but also down-regulation in gliomaassociated microglia/macrophages (GAMs). Notably, none of previous studies investigated oligodendroglial tumours.…”
Section: Tspo In Gliomasmentioning
confidence: 99%
“…It is important to note that Western blot results demonstrated high TSPO levels in the rodent glioma cell line 9L and C6, whereas TSPO expression was undetectable in murine GL261 glioma cells. Although high levels of TSPO density have been extensively reported in malignant brain tumors and successfully correlated to tumor proliferation and grade, one should also consider the existence of TSPO-negative gliomas (37). The differences observed between the treated and untreated groups relate to the higher degree of infiltration of CD11b-positive immune cells and GFAP-positive astrocytes in the tumors of ErPC3-treated animals with respect to control tumors (Fig.…”
Section: Discussionmentioning
confidence: 92%